Anxiety and cognition. Issue 4 (July 2014) - Maloney, Erin A.; Sattizahn, Jason R.; Beilock, Sian L.
<x xml:space="preserve">Abstract</x> In this review we discuss the interplay between anxiety and cognition, illustrating how anxiety can compromise performance on cognitively‐demanding tasks and lead people to perform below their ability. Using math anxiety and test anxiety as examples, we highlight key findings from psychology, cognitive science, and neuroscience, to show that how one approaches an anxiety‐inducing situation can have a large impact on how that person ultimately performs. We end by discussing who is most susceptible to anxiety‐induced poor performance and suggest promising techniques which may help to reduce the negative impact of anxiety on performance. WIREs Cogn Sci 2014, 5:403–411. doi: 10.1002/wcs.1299 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.